1992
DOI: 10.7326/0003-4819-117-2-117
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Course of Idiopathic Dilated Cardiomyopathy

Abstract: These population-based data challenge the clinical perception of the clinical course of idiopathic dilated cardiomyopathy based on referral practice prognostic studies and suggest that the clinical course of this condition may be more favorable than previously recognized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
63
0
5

Year Published

1994
1994
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(71 citation statements)
references
References 40 publications
2
63
0
5
Order By: Relevance
“…[28][29][30] The most common initial manifestation is heart failure, which occurs in 75% to 85% of patients. 19,30,31 Some patients affected by IDCM have prevalent rhythm disturbances. Olson et al 32 reported that heritable SCN5A defects are associated with susceptibility to early-onset IDCM and AF.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] The most common initial manifestation is heart failure, which occurs in 75% to 85% of patients. 19,30,31 Some patients affected by IDCM have prevalent rhythm disturbances. Olson et al 32 reported that heritable SCN5A defects are associated with susceptibility to early-onset IDCM and AF.…”
Section: Discussionmentioning
confidence: 99%
“…Most prior studies of the natural history and prognosis of IDC have been based on populations of selected patients from referral centers, [1][2][3][4][5][6][7][8][9] and therefore, on the basis of different levels of care and management, various prognoses would be expected. The clinical outcome and perception of prognostic factors in IDC is profoundly affected by a bias in patient selection.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have shown a poorer prognosis of patients with Chagas cardiomyopathy in comparison to patients with IDC among several etiologies of heart failureIntroduction Idiopathic Dilated Cardiomyopathy (IDC) has an incidence of 17.9/100,000 inhabitants in the general population 1 . It is the third cause of chronic systolic heart failure 2 , with an annual mortality of 95% in populationbased series and 69% in tertiary referral cohorts 3 .…”
mentioning
confidence: 99%